Comparative net cost impact of the utilization of panitumumab versus cetuximab for the treatment of patients with metastatic colorectal cancer in Canada. (1st February 2016) - Pettigrew, M.; Kavan, P.; Surprenant, L.; Lim, H. J.
Abstract: Objective: Clinical practice guidelines support the use of the epidermal growth factor receptor (EGFR) inhibitors panitumumab and cetuximab for the treatment of metastatic colorectal cancer (mCRC) after failure of other chemotherapy regimens, based on significant clinical benefits in patients with wild-type KRAS. The purpose of the analysis was to compare provincial hospital costs when using panitumumab vs cetuximab with or without irinotecan in this patient population using a Net Impact Analysis (NIA) approach. Methods: The NIA determined the total per patient cost of the reimbursed regimens of panitumumab vs cetuximab in British Columbia, Alberta, Manitoba, Ontario, and Québec. Utilization of healthcare resources related to EGFR inhibitor infusions, follow-up monitoring, and treatment of adverse events (AEs) were also included. Healthcare resource use including drugs, medical supplies, laboratory testing, oncology infusion time, and healthcare professionals' time was obtained through expert consultation and the use was then multiplied by the province-specific cost of each resource. Numerous sensitivity analyses were conducted. Results: Based on the dosing regimens in place in each province, the total annual per patient cost of panitumumab ranged from $22, 203–$32, 600, while the total annual per patient cost of cetuximab treatment varied from $30, 321–$40, 908. Treatment with panitumumab resulted in lower costs in all cost categories including drug acquisition, infusion preparation/administration, patient monitoring, and AE management. Per patient savings with panitumumab ranged from a low of $3815 in British Columbia to a high of $10, 603 in Ontario. In sensitivity analyses, panitumumab remained cost saving in all scenarios where the savings ranged from $150–$16, 006 per patient. Conclusions: Treating chemorefractory mCRC patients with panitumumab rather than cetuximab reduced healthcare resource costs. Provincial healthcare savings achieved with the use of panitumumab could potentially be re-allocated to other cancer treatments, although further study would be needed to validate this assumption.